Outcome of Twin Pregnancies Complicated by a Neural Tube Defect. (7th May 2018) - Ross, Vanessa; Reidy, Karen; Doyle, Lex W.; Palma-Dias, Ricardo; Umstad, Mark P.
Abstract : Twin pregnancies discordant for neural tube defects (NTD) is a management dilemma. Risks of preterm delivery from polyhydramnios must be balanced with the risks of selective termination (ST) of the anomalous fetus. We investigated the prevalence of twin pregnancies discordant for NTD and the rate of pregnancy complications in our institution over a 10-year period. Cases were obtained by searching the hospital ultrasound database and findings were confirmed by expert review of ultrasound images. Outcomes of ST and expectant management were assessed. Each unaffected co-twin was assigned to three consecutive twin pregnancy controls matched by chorionicity and maternal age. Primary outcome was birth before 34 weeks' gestation. Secondary outcomes were small for gestational age, mode of delivery, neonatal unit admission, and neonatal death. In total, 13 pregnancies were identified as potential cases. Of these, 11 were included in the analysis: 9 dichorionic diamniotic and 2 monochorionic diamniotic twins. Seven cases had ST and four were managed expectantly. We found 100% (4/4) of expectantly managed pregnancies delivered <34 weeks compared with 14% (1/7) of the ST group ( p = .015). Polyhydramnios complicated three expectantly managed pregnancies and one pregnancy in the ST group. The birthweight SD score of all unaffected co-twins was ≥-2. The case–control analysis showed a higher rate of polyhydramnios in twin pregnancies discordant for NTD compared with controls, but little evidence for differences between groups in delivery rates <34 weeks, birthweight, neonatal unit admission, or neonatal death. ST warrants serious consideration to avoid potential complications to the unaffected co-twin.